History development Central Asian project “One belt one put” (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
This article explores the “Belt and Road Initiative” proposed by China as a strategy for establishing economic and trade connections among Asian, European, and African countries. Special attention is given to the commitment to creating a sustainable and innovative “Green Silk Road,” involving collaboration in the fields of ecology and sustainable development. Overall, the “Belt and Road Initiative” is considered as a promising approach to the development of global economic relations, capable of fostering cultural and national convergence.
Keywords: The history of the creation of the Belt and Road Initiative (BRI), the Economic Silk Road, the Maritime Silk Road, the Green Silk Road, and joint projects within this program, cultural heritage